KNOWLEDGE MANAGEMENT, INNOVATIVENESS, AND ORGANIZATIONAL PERFORMANCE: EVIDENCE FROM SERBIA - Slavković, Marko; Babić, Verica (Economic Annals, 2013)
The importance of knowledge management and its contribution to organizational performance and innovativeness has been the subject of many studies and is increasingly gaining recognition worldwide. Our study analyses the impact of knowledge management on perceived organizational performance and innovativeness in the context of the Serbian economy. The results of the empirical research on leading Serbian firms demonstrates the direct and positive effect of knowledge management. The regression results show that knowledge management generally has a positive effect on organizational performance. Also, the results show that knowledge management is positively related to the different dimensions of organizational innovation (process innovation and administrative innovation). The mediating effects of process innovation and administrative innovation on the relationship between knowledge management and organizational performance are only partially supported.